The Study Of Artificial Intelligence’s Impact On Project Management And Employee Performance - Xu Bo; Oyyappan (Revista Electronica de Veterinaria, 2024)
This thesis study examined the use of artificial intelligence (AI) in project management with an emphasis on the effects on employees. Artificial intelligence (AI) has the potential to enhance decision-making, boost productivity, and streamline project management in the future. This thesis’s primary goal was to look at how artificial intelligence has affected project managers and the workers they hire. In this study, the researchers look at the advantages and disadvantages of using artificial intelligence (AI), how it changed the responsibilities of project managers and team members, and what ethical issues arose from using AI in project management. The study comprised a literature review in addition to semi-structured interviews with project managers from Greece and Sweden. This was carried out to provide a complete picture. The results show that working people may benefit greatly from the integration of artificial intelligence into project management in several ways, such as decreased effort, improved accuracy, and enhanced insights. On the other hand, ethical issues and employee training need to be thoroughly investigated before artificial intelligence was used.